Декоративна зброя на гуцульщині у ХVIII-XIX cт. (історія, типологія) - Дядюх-Богатько, Н. (Народна творчість та етнографія, 2008)
Decorative features of functional arms group are being demonstrated within chronological and regional boundaries. The technological cycles of arms production, decoration and ritual use in the context of traditional culture of Hutsul regions are examined.